Interference of light, temperature, depth of sowing and straw on germination and emergency of Murdannia nudiflora - Luz, Flávia Nayane; Yamashita, Oscar Mitsuo; Ferraresi, Danilo Aparecido; de Carvalho, Marco Antônio Camillo; Campos, Ostenildo Ribeiro; Koga, Paulo Sergio; Massaroto, João Aguilar (Comunicata Scientiae, 2014)
Murdannia nudiflora, also known as trapoerabinha has been reported in recent years, as animportant weed in soybean crops under no-tillage in Brasil, due to its highly competitive with crops,poor control and rapid infestation. The present work was to study germination of seeds under lightconditions (and without) and temperature (20, 25 and 30 °C), and the emergence in straw (withand without) and sowing depth (0, 0, 1.0, 2.0, 3.0, 4.0 and 8.0 cm). The experimental design wascompletely randomized for all experiments. The species studied presents photoblastism preferred,with higher germination under light. Depths greater than 1.0 cm and the presence of mulch on thesoil surface affect the emergence of seedlings of this species.